America's fight over water : the environmental and political effects of large-scale water systems - Wehr, Kevin, 1972- (American popular history and culture (Routledge (Firm)), 2004)
This book inquires into the relations between society and its natural environment by examining the historical discourse around several cases of state building in the American West: the construction of three high dams from 1928 to 1963.